310 Ruptured sinus of Valsalva aneurysm as a rare cause of sisto-diastolic murmur: role of multimodality imaging in diagnosis and surgical planning. (8th December 2021) - De Luca, Antonio; Fiocco, Alessandro; Restivo, Luca; Poletti, Angela; Faganello, Giorgio; Bussani, Rossana; Sinagra, Gianfranco
Abstract: : A 27-year-old man had an incidental finding of sisto-diastolic murmur during a screening medical evaluation. Transthoracic and subsequent transesophageal echocardiography revealed a saccular enlargement of non-coronary (NC) sinus of Valsalva. The aneurysm extended into the right atrium (RA) and presented a large wall discontinuity, with continuous sisto-diastolic flow from the aorta to the right atrium. Computed tomography confirmed the findings and excluded other associated abnormalities. The patient underwent urgent surgical intervention. Intraoperatively, findings reported a floppy and cribrose saccular aneurysm sprouting from the NC sinus inside the RA. The correction turned out to be very challenging due to the close connection between the aneurysmal wall and the tricuspid valve (TV) and aortic valve (AV) annuli. The aortic NC sinus was excised and replaced with a Dacron patch. Damaging of the TV septal leaflet required repair through a consolidating suture involving the septal leaflet of TV and the corresponding annular insertion. AV replacement was also needed due to damage of the AV NC cusp. No complications occurred during the postoperative stay. Histopathology revealed severe atrophy of muscular and elastic fibres of the aortic wall, elastic fiber fragmentation, replacement fibrosis and extensive deposition of mucopolysaccharides. : Sinus of Valsalva aneurysm (SoVA) is a rare condition characterized by an enlargement of the aortic root between the aortic valve and the sinotubular junction. SoVA can be either congenital, as a consequence of weakness of the elastic lamina, or acquired, due to infective, degenerative, or traumatic conditions. A prevalence of 0.09% was described in autopsy series and males are more frequently affected. Acute rupture of SoVA requires emergent surgery because of acute life-threatening haemodynamic instability. Congenital and chronic ruptured SoVA could be asymptomatic. Nevertheless, such incidental finding requires urgent surgical correction due to the possibility of unexpected further rupture, generating massive left-right shunt. The close relationship with nearby anatomical structures is a major issue which should be taken into account. In this perspective multimodality imaging is of paramount importance, allowing for a fine surgical planning and avoidance of complications.